Behaviour of stainless steel beam-to-column joints-part 2: Numerical modelling and parametric study. (January 2019) - Elflah, Mohamed; Theofanous, Marios; Dirar, Samir
Abstract: This paper reports a detailed numerical (FE) study on planar stainless steel beam-to-column joints. A nonlinear FE model is developed and validated against the first set on full-scale tests on stainless steel beam-to-column joints reported in the companion paper. The FE model is shown to accurately replicate the experimentally determined, initial stiffness, ultimate resistance, overall moment-rotation response and observed failure modes. Parametric studies are conducted to obtain the moment-rotation characteristics of a wide range of beam-to-column joints classified as semi-rigid and/or partial strength. Due to the low ductility of the bolts compared to the high ductility exhibited by all other stainless steel joint components, in all cases the strength and ductility of the simulated joints is limited by the failure of the connecting bolts. The design rules for stainless steel connections, which are based on the specifications of EN 1993-1-8 for carbon steel joints, are reviewed and are found to be overly conservative in terms of strength and inaccurate in terms of stiffness thus necessitating the development of novel design guidance in line with the observed structural response. These conclusions are in agreement with the ones reported in the companion paper. Highlights: The papers reports a comprehensive FE study on stainless steel beam-to-column joints Modelled joints possess excellent rotation capacity and significant over strength Current design standards do not accurately predict the observed failure mode Current design standards are assessed and found overly conservative in the strength prediction of stainless steel joints The development of new design rules in accordance with the observed response is warranted